Antibacterial Activity of Ethanol Extract of Betel Leaf (Piper betle L.) Against Some Food Borne Pathogens - Hoque, M Mahfuzul; Rattila, Shemona; Shishir, M Asaduzzaman; Bari, M L; Inatsu, Y; Kawamoto, S (Bangladesh Journal of Microbiology, 2012)
The ethanol extract of Betel leaf (Piper betle L.), an indigenous climber plant of Bangladesh was screened for its antibacterial activity against some foodborne pathogens viz. Vibrio cholerae ATCC 6395, E. coli ATCC 25922, E. coli O157:H7 NCTC 12049, Shigella dysenteriae-1 MJ-84 and Staphylococcus aureus ATCC 25923. Experimental findings revealed that the ethanol extract of betel leaves potentially inhibit the growth of these foodborne pathogens. Minimum inhibitory concentration (MIC) was ranged from 0.625% (w/v) to 0.75% (w/v). The ethanol extract of betel leaf showed the highest MIC values for E. coli ATCC 25922 (0.625 mm), Vibrio cholera ATCC 6395 (0.625 mm), and Staphylococcus aureus ATCC 25923 (0.625 mm). It was revealed that the antibacterial activity was highest at around neutral pH and at moderate temperature. The highest temperature (100°C) and the pH (10.0) treated ethanol extract showed a little less activity than the maximum activity at moderate temperature and at neutral pH, suggesting that the ethanol extract of the betel leaf was to some extent high temperature and high pH tolerant. The ethanol extract of betel leaf might have a potential application as natural food preservative to improve the microbiological safety of the foods. DOI: http://dx.doi.org/10.3329/bjm.v28i2.11817 Bangladesh J Microbiol, Volume 28, Number 2, December 2011, pp 58-63